Persian culinary metaphors: a cross-cultural conceptualization - Zahra Khajeh; Imran-Ho-Abdullah (Penerbit UKM, 2012)
Studies concerning the metaphorical use of language deal with metaphorical units from two particular perspectives: a mapping from one cognitive domain to another domain, and a grounding of the mapping as a reflection within image schema. The present study demonstrates the pervasiveness of culinary metaphors in Persian social and cultural interaction hypothesizing that related food metaphors may single out the unique status of eating/food in Persian culture and society. Investigating the metaphorical conceptualization of “THOUGHT AS FOOD”, TEMPERAMENT AS FOOD, and LUST AS FOOD within the MIND IS BODY concept is primarily based on the assumption that thought, human disposition, and sexual desires are in fact closely interrelated. Utilizing a particular conceptual metaphor model (Lakoff & Johnson, 1980, 1999; Ahrens, 2002) the image schema and proposition schema of related food metaphors are investigated in order to analyze cultural variations across Persian and English. The researchers suggest that cultural cognition which is distributed across the minds in a cultural group plays a key role as the source of cross-cultural variations.